SISTEM PENDUKUNG KEPUTUSAN PENENTUAN PELANGGAN TERBAIK DI CV. BALI MEDIA - Putra, I Gede Jana Adi; Suyasa, I Putu Buda (Jurnal Ilmiah Sains Sosial, Kewirausahaan dan Kebudayaan, 2023)
Decision Support Systems are interactive information systems that provide information, modeling and data manipulation. This system is used to assist decision making in semi-structured situations and unstructured situations. As a result of the company's annual target which is still difficult to achieve, it is also feared that consumers will switch to other companies that may have similar products at lower prices. Therefore, to increase consumer buying energy for the products being sold. The award given to the best customer can be in the form of a reseller price. Such things will make it difficult for customers to divert their eyes to other companies that both sell the same product. For the calculation method itself, it uses the SAW method as a decision support for selecting the best customer whose decision-making technique has a calculation of weighting criteria that is not too complex, so that it is easy for writers and readers to learn. From the results of the research, an application for driving decisions was produced in the hope of producing the best customer decisions on CV. BaliMedia. by determining the Max (Highest Data) and Min (Lowest Data) values from each of the data categories above and determining the sub-normalization that will be used as a reference for normalized data.